The Detection Rate of Associated Mg ii Absorption Lines in Quasars Depends on Their Radio Emission - Zhi-Fu Chen; Luis C. Ho (The Astrophysical Journal)
In active galactic nuclei, jet-driven feedback plays a significant role in influencing the properties of gas within their host galaxy and the circumgalactic medium. By combining observations from the Very Large Array Sky Survey, the Faint Images of the Radio Sky at Twenty-cm, the LOFAR Two Meter Sky Survey, and the Sloan Digital Sky Survey (SDSS), we assembled a sample of 3141 radio-loud quasars, among which 418 exhibit Mg ii -associated absorption lines in their SDSS spectra. We classify these quasars into evolutionary stages based on their radio spectral shapes. Our analysis reveals that evolved quasars exhibit a significantly higher incidence of Mg ii -associated absorption lines compared to younger sources, particularly among quasars with “nonpeaked” radio spectra, which show an incidence of Mg ii -associated absorbers approximately 1.7 times greater than that of gigahertz-peaked spectrum sources. This observation can be explained effectively by jet-driven feedback. As quasars age, their jets expand and expel substantial amounts of gas from smaller scales to larger scales, ultimately reaching the circumgalactic medium. The gas expelled from the inner regions and distributed over larger scales results in a greater coverage fraction of absorbing gas. Consequently, evolved quasars exhibit a higher incidence of Mg ii absorption lines.